Possible Abscopal Effect Observed in Frontal Meningioma After Localized IMRT on Posterior Meningioma Resection Cavity Without Adjuvant Immunotherapy - Golub, Danielle (Front Oncol, 2019)
Background: Localized radiation therapy (RT) is known to infrequently cause off-target or “abscopal” effects at distant metastatic lesions. The mechanism through which abscopal effects occur remains unknown, but is thought to be caused by a humoral immune response to tumor-specific antigens generated by RT. Combination treatment regimens involving RT and immunotherapy to boost the humoral immune response have demonstrated synergistic effects in promoting and accelerating abscopal effects in metastatic cancer. Nevertheless, abscopal effects, particularly after RT alone, remain exceedingly rare. Case Presentation: We report the case of an 84-year-old man with an atypical meningioma, who demonstrated a radiographically significant response to an untreated second intracranial lesion, likely also a meningioma, after intensity-modulated radiation therapy (IMRT) to a separate, detatched resection cavity. Serial annual MRI imaging starting at 2- to 3.5-year (most recent) post-IMRT follow-up demonstrated a persistent decrease in both tumor size and surrounding edema in the untreated second lesion, suggestive of a possible abscopal effect. Conclusions: We describe here the first report of a potential abscopal effect in meningioma, summarize the limited literature on the topic of abscopal effects in cancer, and detail the existing hypothesis on how this phenomenon may occur and possibly relate to the development of future treatments for patients with metastatic disease.